ELONG UGI: KAJIAN ESTETIKA DALAM PANDANGAN VLADIMIR BRAGINSKY - Uniawati Uniawati (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
This paper describes the aesthetic values of elong ugi "Ala Masea-Sea" by using the concept of beauty in Vladimir Braginsky's view. There are three levels of beauty according to Braginsky, namely; the beauty sphere, the utility sphere, and the functional sphere (refinement). These three levels of spheres are the basis for analysis to answer the three main problems that are formulated in this article. The results of the analysis showed that the elong ugi "Ala Masea-Sea" fulfills two spheres, namely the beauty spheres and the faedah spheres. The functional sphere or the highest sphere in terms of the beauty of a work is not contained in elong ugi "Ala Masea-Sea". However, elong ugi "Ala Masea-Sea" as a classical Bugis literature shows a strong aesthetic value.